Repeatability and Reproducibility of Microdosimetry With a Mini-TEPC - Bianchi, A.; Selva, A.; Colautti, P.; Petringa, G.; Cirrone, P.; Reniers, B.; Parisi, A.; Vanhavere, F.; Conte, V. (Frontiers in Physics, 2021)
Experimental microdosimetry measures the energy deposited in a microscopic sensitive volume (SV) by single ionizing particles traversing the SV or passing by. The fundamental advantage of experimental microdosimetry over the computational approach is that the first allows to determine distributions of energy deposition when information on the energy and nature of the charged particles at the point of interest is incomplete or fragmentary. This is almost always the case in radiation protection applications, but discrepancies between the modelled and the actual scenarios should be considered also in radiation therapy. Models for physical reality are always imperfect and rely both on basic input data and on assumptions and simplifications that are necessarily implemented. Furthermore, unintended events due to human errors or machine/system failures can be minimized but cannot be completely avoided. Though in proton radiation therapy (PRT) a constant relative biological effectiveness (RBE) of 1.1 is assumed, there is evidence of an increasing RBE towards the end of the proton penetration depth. Treatment Planning Systems (TPS) that take into account a variable linear energy transfer (LET) or RBE are already available and could be implemented in PRT in the near future. However, while the calculated dose distributions produced by the TPS are routinely verified with ionization chambers as part of the quality assurance program of every radiotherapy center, there is no commercial detector currently available to perform routine verification of the radiation quality, calculated by the TPS through LET or RBE distributions. Verification of calculated LET is required to make sure that a complex robustly optimized plan will be delivered as planned. The scientific community is coming to conclusion that a new domain of Quality Assurance additionally to the physical dose verification is required, and microdosimetry can be the right approach to address that. A first important prerequisite is the repeatability and reproducibility of microdosimetric measurements. This work aims at studying experimentally the repeatability and reproducibility of microdosimetric measurements performed with a miniaturized Tissue Equivalent Proportional Counter (mini-TEPC) in a 62 MeV proton beam. Experiments were carried out within 1 year and without propane gas recharging and by different operators. RBE was also calculated by applying the Loncol’s weighting function r(y) to microdosimetric distributions. Demonstration of reproducibility of measured microdosimetric quantities y¯F, y¯D and RBE10 in 62 MeV proton beam makes this TEPC a possible metrological tool for LET verification in proton therapy. Future characterization will be performed in higher energy proton beams.